Análisis de la calidad de agua y presencia de microplásticos en la parte alta media y baja del río Pumacunchi en la provincia de Cotopaxi, período 2022. - Narváez Chiliquinga, Jonathan José (2022)
Water pollution, due to population growth, industrial and agricultural activities without environmental responsibility and the polymer derivatives excessive use are a worldwide problem. This research project is based on the water quality determination and microplastics (MPs) identification into Pumacunchi river, located in the Cotopaxi province, Saquisilí canton, at three strategic points (P1 Cochapamba, P2 Canchagua and P3 Chantilín). For this, it was applied the Canadian Water Quality Index (CCME_QWI) with 10 parameters: Arsenic, Nitrates, Turbidity, Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), dissolved oxygen, Nitrates as NO3, Electrical Conductivity (EC), Total Dissolved Solids (TDS) and pH, taking as reference thresholds established in national and international regulations, on the other hand, it was performed the microplastics identification, by means microfiltration with two filters, it was analyzed their morphology type, through observation. The got results show, what the water quality, in P1 presents an 2 index, placing it into a good water quality, the parameters that exceed the maximum permissible limits (LMP) were: DBO (>5mg/L) and dissolved oxygen (> 4mg/L). P2 has an 86 index, indicating good water quality, the parameters, what exceed the LMP are: DBO (>5mg/L) and Dissolved Oxygen (>4mg/L). P3 presents a 67 index that indicates a regular water quality, the parameters, what exceed the LMP are: DBO (>5mg/L), Dissolved Oxygen (>5mg/L), EC (>750us/cm), TDS (>500mg/L), Arsenic (>0.1mg/L). Into two samplings results made for microplastics were: the first sampling in P1 and P2 were identified microplastics with fiber-like morphology, representing 100% in the entire analysis thereof, in P3 microplastics with fiber-like morphology and fragment-like morphology were found, representing that 89% corresponds to fiber and 11% corresponds to microplastic fragments. For the second sampling, P1 was identified microplastics with fiber-like morphology and fragment-like morphology, characterizing that 93% corresponds to fibers and 7% corresponds to microplastic fragments, likewise, point 2 found microplastics with fiber-like morphology and fragment, determining that 89% concerns microplastic fibers and 11% corresponds to microplastic fragments and finally, the P3 of got microplastics correspond to fibers revealing that 100% of analyzed microplastics are fibers. Microplastics with fiber-like morphology are the ones that predominate in the Pumacunchi River. Fibers are usually the main microplastic pollution type, which found into aquatic environments. Finally, the got results should be shared with the communities and competent authorities from Saquisilí canton, so that they are aware of water quality current state and, most importantly, the microplastics presence in the river, so that, it achieved to incentive possible bioremediation, which. helps reduce pollution. In turn, the project managed to contribute to more research about the microplastics presence in the rivers.